Effects of repetitive mechanical tactile stimulation interventions with stationary and moving patterns on paired-pulse depression - Hiraku Watanabe; Sho Kojima; Naofumi Otsuru; Hideaki Onishi (BMC Neuroscience)
Abstract Background Repetitive somatosensory stimulation (RSS) reduces paired-pulse depression (PPD), reflecting GABAergic inhibition in the primary somatosensory cortex (S1). This effect may vary by tactile stimulation pattern. Therefore, this study aimed to clarify the effects of RSS intervention with stationary and moving pattern tactile stimulation on PPD. Results In a crossover study of 15 healthy males, RSS with a stationary pattern showed a non-significant trend toward increased PPD (corrected p = 0.088), while the moving pattern showed no effect. A strong negative correlation was found between baseline PPD and its change rate (r = − 0.837, p < 0.001), indicating that greater baseline S1 inhibition predicted a larger reduction after RSS. Conclusion RSS effects on GABAergic inhibition in S1 depend on the tactile stimulation pattern, emphasizing the importance of tactile stimulus design in modulating somatosensory cortex activity.